2015 IEEE 17th Electronics Packaging and Technology Conference (EPTC) 2015
DOI: 10.1109/eptc.2015.7412380
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cycling reliability analysis of an anisotropic conductive adhesive attached large-area chip with area array configuration

Abstract: The reliability of adhesive flip chip attachments was studied. A large-area chip with a great number of contacts was attached onto a flexible polyimide substrate using anisotropic conductive adhesive film (ACF). The test samples were manufactured using various bonding forces and the reliability of the assemblies was examined using a thermal cycling test. Two temperature change rates were used in the cycling test to study the effect of the change rate on the observed failure times and modes. The results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…[1,2] Previous reliability studies of ACA interconnects have shown failures that typically stem from its thermo-mechanical performance rather than the conductive particles. [28][29][30] Hence, electrical resistance has been the main focus of this work, offering the possibility of controlling the conductive particles in ACA interconnects. Further investigation into the reliability of the proposed ACA interconnection approach, however, is crucial to understand the interconnect robustness under operating conditions.…”
Section: Aca Interconnects Using Nano Ag Inkmentioning
confidence: 99%
“…[1,2] Previous reliability studies of ACA interconnects have shown failures that typically stem from its thermo-mechanical performance rather than the conductive particles. [28][29][30] Hence, electrical resistance has been the main focus of this work, offering the possibility of controlling the conductive particles in ACA interconnects. Further investigation into the reliability of the proposed ACA interconnection approach, however, is crucial to understand the interconnect robustness under operating conditions.…”
Section: Aca Interconnects Using Nano Ag Inkmentioning
confidence: 99%